Communication skills in pharmacy practice : a practical guide for students and practitioners - Beardsley, Robert S.; Skrabal, Maryann Z.; Kimberlin, Carole L. (Philadelphia : Wolters Kluwer, 2020)
Newly focused on the practical communications skills student pharmacists need for effective practice, this updated Seventh Edition--now in full color-- reflects new ACPE standards, including up-to-date coverage of the PPCP model, co-curricular experiences, interprofessional interaction and collaboration, and professional development. Practical, easy-to-use, and packed with relevant case studies and coverage of the latest advances in the field, this edition is ideal for the foundational course and pre-experiential training. Expanded emphasis on communication skill application helps students master the knowledge and skills they need for pharmacy practice. Additional content added on motivational interviewing, e-commerce, contemporary ethical issues (such as medical marijuana and opioid abuse), and student-preceptor and pharmacist-management communication issues. Full-color design with new diagrams and figures enhances readability. Additional case studies from diverse settings prepare students to deal with the wide range of situations they will encounter in practice. Stronger emphasis on assessing communication skills includes coverage of patient surveys and colleague observers. Expanded coverage on choosing effective patient education materials and communicating with Limited English Proficiency (LEP) patients prepares students for professional practice. Revised review questions, chapter-ending review cases, and references help students master the material.
1. Patient-Centered Communication in Pharmacy Practice -- 2. Principles and Elements of Interpersonal Communication -- 3. Nonverbal Communication -- 4. Barriers to Communication -- 5. Listening and Empathic Responding -- 6. Assertiveness -- 7. Interviewing and Assessment -- 8. Helping Patients Manage Therapeutic Regimens -- 9. Medication Safety and Communication Skills -- 10. Strategies to Meet Specific Needs -- 11. Communicating with Children about Medicines -- 12. Interprofessional Collaboration and Effective Communication Skills -- 13. Digital Communication in Health Care -- 14. Ethical Behavior When Communicating with Patients.
Includes bibliographical references and index.
Keywords: Pharmacists; Communication; Professional-patient relations